AGRICULTURAL LAND USE AND FOOD SECURITY IN PAKISTAN: A STRUCTURAL EQUATION MODELING APPROACH - B. Pervaiz; N. Li; M. Q. Manzoor (Journal of Animal and Plant Sciences, 2019)
Pakistan is an agrarian country and has diverse resources of agricultural land. The current study has been conducted in the province of Punjab with an aim to explore the association among agricultural farm area, agricultural farm infrastructure, agricultural farming community, agricultural output, and the issues of food security in the context of bringing improvement in the living standard of farmers and the rural poor. For this purpose, a field survey was conducted across Punjab and data from 300 households was collected under multi-stage clustered sampling technique on a detailed questionnaire. Structural Equation Modeling (SEM) technique was employed to incorporate the significance of special situations for improved understanding. The results showed that secure land administration and tenancy improved the farm production. Meanwhile, farm area, modern production technology and safeguards against natural disasters were important for increasing farmers’ income. The poor nutritional level of rural community was found to be associated with its agricultural profitability which suggested compromised standard of living. Food security in Pakistan appeared to be directly affected by agricultural output and indirectly by appropriate farm area which in turn was directly linked with standard of living. The government may like to improve land governance and implement such policies which increase farmers’ profitability for their better nutrition and standard of living.
Keywords: Food security; Land use; SEM; Standard of living; Farm area; Pakistan